Актуальні проблеми змісту системи адміністративного права - Мінка, Т.П. (Часопис Київського університету права, 2009)
Статья посвящена проблемам системы и структуры административного права Украины. На основании исторического анализа научных взглядов на систему административного права, учитывая труды украинских ученых в этой сфере, так же реформирование административного права, пересмотр его предмета и объекта, автор приводит собственную концепцию системы административного права. Ключевые слова: система права, административное право, система административного права. The article is devoted the problems of the system and structure of administrative law of Ukraine. On the basis of historical analysis of scientific looks to the system of administrative law, taking into account labours of the Ukrainian scientists in this sphere, similarly reformation of administrative law, revision of his object and object, an author brings own conception over of the system of administrative law. Keywords: system of right, administrative law, system of administrative law.